From Maps to Models: Augmenting the Nation's Geospatial Intelligence Capabilities - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2016)
The United States faces numerous, varied, and evolving threats to national security, including terrorism, scarcity and disruption of food and water supplies, extreme weather events, and regional conflicts around the world. Effectively managing these threats requires intelligence that not only assesses what is happening now, but that also anticipates potential future threats. The National Geospatial-Intelligence Agency (NGA) is responsible for providing geospatial intelligence on other countries2014assessing where exactly something is, what it is, and why it is important2014in support of national security, disaster response, and humanitarian assistance. NGA2019s approach today relies heavily on imagery analysis and mapping, which provide an assessment of current and past conditions. However, augmenting that approach with a strong modeling capability would enable NGA to also anticipate and explore future outcomes. A model is a simplified representation of a real-world system that is used to extract explainable insights about the system, predict future outcomes, or explore what might happen under plausible what-if scenarios. Such models use data and\/or theory to specify inputs (e.g., initial conditions, boundary conditions, and model parameters) to produce an output. From Maps to Models: Augmenting the Nation's Geospatial Intelligence Capabilities describes the types of models and analytical methods used to understand real-world systems, discusses what would be required to make these models and methods useful for geospatial intelligence, and identifies supporting research and development for NGA. This report provides examples of models that have been used to help answer the sorts of questions NGA might ask, describes how to go about a model-based investigation, and discusses models and methods that are relevant to NGA2019s mission.

Fundamental Research in High Energy Density Science - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2023)
High energy density (HED) science has critical applications for society from fusion energy to sustaining the US nuclear deterrent, while also contributing to broader scientific questions such as understanding planets and their origins. The next decade of HED science will be instrumental to growing our understanding and in the development of new technologies and processes. Fundamental Research in High Energy Density Science identifies key challenges and science questions for the field for the coming decade and proposes ways to address them.

Plasma Science: Enabling Technology, Sustainability, Security, and Exploration - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2021)
Plasma Science and Engineering transforms fundamental scientific research into powerful societal applications, from materials processing and healthcare to forecasting space weather. Plasma Science: Enabling Technology, Sustainability, Security and Exploration discusses the importance of plasma research, identifies important grand challenges for the next decade, and makes recommendations on funding and workforce. This publication will help federal agencies, policymakers, and academic leadership understand the importance of plasma research and make informed decisions about plasma science funding, workforce, and research directions.

Advancing Chemistry and Quantum Information Science: An Assessment of Research Opportunities at the Interface of Chemistry and Quantum Information Science in the United States - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2023)
The field of quantum information science (QIS) has witnessed a dramatic rise in scientific research activities in the 21st century as excitement has grown about its potential to revolutionize communications and computing, strengthen encryption, and enhance quantum sensing, among other applications. While, historically, QIS research has been dominated by the field of physics and computer engineering, this report explores how chemistry - in particular the use of molecular qubits - could advance QIS. In turn, researchers are also examining how QIS could be used to solve problems in chemistry, for example, to facilitate new drug and material designs, health and environmental monitoring tools, and more sustainable energy production. Recognizing that QIS could be a disruptive technology with the potential to create groundbreaking products and new industries, Advancing Chemistry and Quantum Information Science calls for U.S. leadership to build a robust enterprise to facilitate and support research at the intersection of chemistry and QIS. This report identifies three key research areas: design and synthesis of molecular qubit systems, measurement and control of molecular quantum systems, and experimental and computational approaches for scaling qubit design and function. Advancing Chemistry and Quantum Information Science recommends that the Department of Energy, National Science Foundation, and other funding agencies should support multidisciplinary and collaborative research in QIS, the development of new instrumentation, and facilities, centralized and open-access databases, and efforts to create a more diverse and inclusive chemical workforce.

Empowering the Defense Acquisition Workforce to Improve Mission Outcomes Using Data Science - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2021)
The effective use of data science - the science and technology of extracting value from data - improves, enhances, and strengthens acquisition decision-making and outcomes. Using data science to support decision making is not new to the defense acquisition community; its use by the acquisition workforce has enabled acquisition and thus defense successes for decades. Still, more consistent and expanded application of data science will continue improving acquisition outcomes, and doing so requires coordinated efforts across the defense acquisition system and its related communities and stakeholders. Central to that effort is the development, growth, and sustainment of data science capabilities across the acquisition workforce. At the request of the Under Secretary of Defense for Acquisition and Sustainment, Empowering the Defense Acquisition Workforce to Improve Mission Outcomes Using Data Science assesses how data science can improve acquisition processes and develops a framework for training and educating the defense acquisition workforce to better exploit the application of data science. This report identifies opportunities where data science can improve acquisition processes, the relevant data science skills and capabilities necessary for the acquisition workforce, and relevant models of data science training and education.

Roundtable on Data Science Postsecondary Education: A Compilation of Meeting Highlights - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2020)
Established in December 2016, the National Academies of Sciences, Engineering, and Medicine's Roundtable on Data Science Postsecondary Education was charged with identifying the challenges of and highlighting best practices in postsecondary data science education. Convening quarterly for 3 years, representatives from academia, industry, and government gathered with other experts from across the nation to discuss various topics under this charge. The meetings centered on four central themes: foundations of data science; data science across the postsecondary curriculum; data science across society; and ethics and data science. This publication highlights the presentations and discussions of each meeting.

Quantum Science Concepts in Enhancing Sensing and Imaging Technologies: Applications for Biology: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2021)
Quantum concepts hold the potential to enable significant advances in sensing and imaging technologies that could be vital to the study of biological systems. The workshop Quantum Science Concepts in Enhancing Sensing and Imaging Technologies: Applications for Biology, held online March 8-10, 2021, was organized to examine the research and development needs to advance biological applications of quantum technology. Hosted by the National Academies of Sciences, Engineering, and Medicine, the event brought together experts working on state-of-the-art, quantum-enabled technologies and scientists who are interested in applying these technologies to biological systems. Through talks, panels, and discussions, the workshop facilitated a better understanding of the current and future biological applications of quantum-enabled technologies in fields such as microbiology, molecular biology, cell biology, plant science, mycology, and many others. This publication summarizes the presentation and discussion of the workshop.

A Research Agenda for Transforming Separation Science - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2019)
Separation science plays a critical role in maintaining our standard of living and quality of life. Many industrial processes and general necessities such as chemicals, medicines, clean water, safe food, and energy sources rely on chemical separations. However, the process of chemical separations is often overlooked during product development and this has led to inefficiency, unnecessary waste, and lack of consensus among chemists and engineers. A reevaluation of system design, establishment of standards, and an increased focus on the advancement of separation science are imperative in supporting increased efficiency, continued U.S. manufacturing competitiveness, and public welfare. A Research Agenda for Transforming Separation Science explores developments in the industry since the 1987 National Academies report, Separation and Purification: Critical Needs and Opportunities. Many needs stated in the original report remain today, in addition to a variety of new challenges due to improved detection limits, advances in medicine, and a recent emphasis on sustainability and environmental stewardship. This report examines emerging chemical separation technologies, relevant developments in intersecting disciplines, and gaps in existing research, and provides recommendations for the application of improved separation science technologies and processes. This research serves as a foundation for transforming separation science, which could reduce global energy use, improve human and environmental health, and advance more efficient practices in various industries.

An Assessment of the Science Proposed for the Deep Underground Science and Engineering Laboratory (DUSEL) - National Research Council (The National Academies Press, 2012)
According to the big bang theory, our Universe began in a state of unimaginably high energy and density, contained in a space of subatomic dimensions. At that time, unlike today, the fundamental forces of nature were presumably unified and the particles present were interacting at energies not attainable by present-day accelerators. Underground laboratories provide the conditions to investigate processes involving rare phenomena in matter and to detect the weak effects of highly elusive particles by replicating similar environments to those once harnessed during the earliest states of the Earth. These laboratories now appear to be the gateway to understanding the physics of the grand unification of the forces of nature. Built to shield extremely sensitive detectors from the noise of their surroundings and the signals associated with cosmic rays, underground facilities have been established during the last 30 years at a number of sites worldwide. To date, the United States' efforts to develop such facilities have been modest and consist primarily of small underground laboratories. However, the U.S. underground community has pushed for larger underground facilities on the scale of major laboratories in other countries. An Assessment of the Deep Underground Science and Engineering Laboratory (DUSEL) addresses this matter by evaluating the major physics questions and experiments that could be explored with the proposed DUSEL. Measuring the potential impact, this assessment also examines the broader effects of the DUSEL in regards to education and public outreach, and evaluates the need associated with developing U.S. programs similar to science programs in other regions of the world.

Data Science: Opportunities to Transform Chemical Sciences and Engineering: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2018)
New technologies and approaches are generating large, diverse data sets, and data science offers the tools that are needed to interrogate, analyze, and manage these data sets. Biology, material sciences, and other fields have embraced data science tools and used them to gain insights into, for example, gene2013environment interactions, molecular mechanisms of disease, and implications of material characteristics on performance. Chemical sciences and engineering have also used data science tools to, for example, monitor and control chemical processes, predict activity depending on chemical structures or properties, and inform business and research decisions. However, data science applications in the chemical sciences and engineering community have been relatively limited, and many opportunities for advancing the fields have gone unexplored. Accordingly, the National Academies of Sciences, Engineering, and Medicine held a workshop to explore opportunities to use data science to transform chemical sciences and engineering on February 27201328, 2018, in Washington, DC. Stakeholders from academia, government, and industry convened to discuss the challenges and opportunities to integrate data science into chemical sciences and engineering practice and data science training for the future chemical sciences and engineering workforce. This publication summarizes the presentations and discussions from the workshop.

Data Science for Undergraduates: Opportunities and Options - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2018)
Data science is emerging as a field that is revolutionizing science and industries alike. Work across nearly all domains is becoming more data driven, affecting both the jobs that are available and the skills that are required. As more data and ways of analyzing them become available, more aspects of the economy, society, and daily life will become dependent on data. It is imperative that educators, administrators, and students begin today to consider how to best prepare for and keep pace with this data-driven era of tomorrow. Undergraduate teaching, in particular, offers a critical link in offering more data science exposure to students and expanding the supply of data science talent. Data Science for Undergraduates: Opportunities and Options offers a vision for the emerging discipline of data science at the undergraduate level. This report outlines some considerations and approaches for academic institutions and others in the broader data science communities to help guide the ongoing transformation of this field.

Communicating Science and Engineering Data in the Information Age - National Research Council (The National Academies Press, 2012)
The National Center for Science and Engineering Statistics (NCSES) of the National Science Foundation (NSF) communicates its science and engineering (S&E) information to data users in a very fluid environment that is undergoing modernization at a pace at which data producer dissemination practices, protocols, and technologies, on one hand, and user demands and capabilities, on the other, are changing faster than the agency has been able to accommodate. NCSES asked the Committee on National Statistics and the Computer Science and Telecommunications Board of the National Research Council to form a panel to review the NCSES communication and dissemination program that is concerned with the collection and distribution of information on science and engineering and to recommend future directions for the program. Communicating Science and Engineering Data in the Information Age includes recommendations to improve NCSES's dissemination program and improve data user engagement. This report includes recommendations such as NCSES's transition to a dissemination framework that emphasizes database management rather than data presentation, and that NCSES analyze the results of its initial online consumer survey and refine it over time. The implementation of the report's recommendations should be undertaken within an overall framework that accords priority to the basic quality of the data and the fundamentals of dissemination, then to significant enhancements that are achievable in the short term, while laying the groundwork for other long-term improvements.

An Assessment of U.S.-Based Electron-Ion Collider Science - National Academies of Sciences, Engineering,; Medicine
Understanding of protons and neutrons, or \

High Magnetic Field Science and Its Application in the United States: Current Status and Future Directions - National Research Council
The Committee to Assess the Current Status and Future Direction of High Magnetic Field Science in the United States was convened by the National Research Council in response to a request by the National Science Foundation. This report answers three questions: (1) What is the current state of high-field magnet science, engineering, and technology in the United States, and are there any conspicuous needs to be addressed? (2) What are the current science drivers and which scientific opportunities and challenges can be anticipated over the next ten years? (3) What are the principal existing and planned high magnetic field facilities outside of the United States, what roles have U.S. high field magnet development efforts played in developing those facilities, and what potentials exist for further international collaboration in this area? A magnetic field is produced by an electrical current in a metal coil. This current exerts an expansive force on the coil, and a magnetic field is \

Communicating Chemistry: A Framework for Sharing Science: A Practical Evidence-Based Guide - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2016)
A growing body of evidence indicates that, increasingly, the public is engaging with science in a wide range of informal environments, which can be any setting outside of school such as community-based programs, festivals, libraries, or home. Yet undergraduate and graduate schools often don2019t prepare scientists for public communication. This practical guide is intended for any chemist 2013 that is, any professional who works in chemistry-related activities, whether research, manufacturing or policy 2013 who wishes to improve their informal communications with the public. At the heart of this guide is a framework, which was presented in the report Effective Chemistry Communication in Informal Environments and is based on the best available empirical evidence from the research literature on informal learning, science communication, and chemistry education. The framework consists of five elements which can be applied broadly to any science communication event in an informal setting.

Solar and Space Physics: A Science for a Technological Society: An Overview - National Research Council (The National Academies Press, 2014)
In 2010, NASA and the National Science Foundation asked the National Research Council to assemble a committee of experts to develop an integrated national strategy that would guide agency investments in solar and space physics for the years 2013-2022. That strategy, the result of nearly 2 years of effort by the survey committee, which worked with more than 100 scientists and engineers on eight supporting study panels, is presented in the 2013 publication, Solar and Space Physics: A Science for a Technological Society. This booklet, designed to be accessible to a broader audience of policymakers and the interested public, summarizes the content of that report.

The Quality of Science and Engineering at the NNSA National Security Laboratories - National Research Council (The National Academies Press, 2013)
The three National Nuclear Security Administration (NNSA) national security laboratories2014Los Alamos National Laboratory (LANL), Lawrence Livermore National Laboratory (LLNL), and Sandia National Laboratories (SNL)2014are a major component of the U.S. government's laboratory complex and of the national science and technology base. These laboratories are large, diverse, highly respected institutions with broad programs in basic sciences, applied sciences, technology development, and engineering; and they are home to world-class staff and facilities. Under a recent interagency agreement between the Department of Energy (DOE), Department of Defense, Department of Homeland Security, and the intelligence community, they are evolving to serve the needs of the broad national security community. Despite this broadening of substance and support, these laboratories remain the unique locus of science and engineering (S&E) for the U.S. nuclear weapons program, including, most significantly, the science-based stockpile stewardship program and the S&E basis for analyzing and understanding nuclear weapon developments of other nations and non-state actors. The National Research Council (NRC) was asked by Congress to assess the quality of S&E and the management of S&E at these three laboratories. The Quality of Science and Engineering at the NNSA National Security Laboratories is the second of two reports produced as part of this study. This report assesses the quality of S&E in terms of the capability of the laboratories to perform the necessary tasks to execute the laboratories' missions, both at present and in the future. The report identifies the following as four basic pillars of stockpile stewardship and non-proliferation analysis: (1) the weapons design; (2) systems engineering and understanding of the effects of aging on system performance; (3) weapons science base; and (4) modeling and simulation, which provides a capability to integrate theory, experimental data, and system design. The Quality of Science and Engineering at the NNSA National Security Laboratories offers a snapshot of the present with an eye to the future. This report discusses the current state of S&E and makes recommendations to maintain robust programs.

Safe Science: Promoting a Culture of Safety in Academic Chemical Research - National Research Council (The National Academies Press, 2014)
Recent serious and sometimes fatal accidents in chemical research laboratories at United States universities have driven government agencies, professional societies, industries, and universities themselves to examine the culture of safety in research laboratories. These incidents have triggered a broader discussion of how serious incidents can be prevented in the future and how best to train researchers and emergency personnel to respond appropriately when incidents do occur. As the priority placed on safety increases, many institutions have expressed a desire to go beyond simple compliance with regulations to work toward fostering a strong, positive safety culture: affirming a constant commitment to safety throughout their institutions, while integrating safety as an essential element in the daily work of laboratory researchers. Safe Science takes on this challenge. This report examines the culture of safety in research institutions and makes recommendations for university leadership, laboratory researchers, and environmental health and safety professionals to support safety as a core value of their institutions. The report discusses ways to fulfill that commitment through prioritizing funding for safety equipment and training, as well as making safety an ongoing operational priority. A strong, positive safety culture arises not because of a set of rules but because of a constant commitment to safety throughout an organization. Such a culture supports the free exchange of safety information, emphasizes learning and improvement, and assigns greater importance to solving problems than to placing blame. High importance is assigned to safety at all times, not just when it is convenient or does not threaten personal or institutional productivity goals. Safe Science will be a guide to make the changes needed at all levels to protect students, researchers, and staff.

Strengthening Data Science Methods for Department of Defense Personnel and Readiness Missions - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2017)
The Office of the Under Secretary of Defense (Personnel & Readiness), referred to throughout this report as P&R, is responsible for the total force management of all Department of Defense (DoD) components including the recruitment, readiness, and retention of personnel. Its work and policies are supported by a number of organizations both within DoD, including the Defense Manpower Data Center (DMDC), and externally, including the federally funded research and development centers (FFRDCs) that work for DoD. P&R must be able to answer questions for the Secretary of Defense such as how to recruit people with an aptitude for and interest in various specialties and along particular career tracks and how to assess on an ongoing basis service members' career satisfaction and their ability to meet new challenges. P&R must also address larger-scale questions, such as how the current realignment of forces to the Asia-Pacific area and other regions will affect recruitment, readiness, and retention. While DoD makes use of large-scale data and mathematical analysis in intelligence, surveillance, reconnaissance, and elsewhere2014exploiting techniques such as complex network analysis, machine learning, streaming social media analysis, and anomaly detection2014these skills and capabilities have not been applied as well to the personnel and readiness enterprise. Strengthening Data Science Methods for Department of Defense Personnel and Readiness Missions offers and roadmap and implementation plan for the integration of data analysis in support of decisions within the purview of P&R.

A View of Global S&T Based on Activities of the Board on Global Science and Technology: Letter Report - National Research Council (The National Academies Press, 2011)
This letter report describes the 2009-2011 activities of the Board on Global Science and Technology (BGST) and provides an initial characterization of the global science and technology landscape that the Board can use as a roadmap to develop future activities. BGST met five times between November 2009 and May 2011. Board meetings were devoted to (1) identifying national security implications of the globalization of S&T, (2) building a baseline understanding of current indicators for the U.S. posture with regard to the evolving global S&T landscape, and (3) developing a BGST engagement strategy. The letter portion of the report summarizes activities of the board in its first year, and also describes some existing approaches to identifying and\/or benchmarking emerging technologies globally. It is followed by 5 appendixes which include three experimental examples of a qualitative approach to benchmarking, and brief descriptions of programs that are part of the National Academies complex, with which BGST has cooperated.